Weak Cytotoxic Activity of Miltefosine Against Clinical Isolates of Acanthamoeba spp - Mrva, M; Garajová, M; Lukáč, M; Ondriska, F (The Journal of parasitology, 2011)
Hexadecylphosphocholine (miltefosine) is an anticancer drug active in vitro against various protozoan parasites, and recently used for the treatment of disseminated Acanthamoeba infection. In the present study, we present results of weak cytotoxic activity of this potential amoebicidal agent for 2 of 3 clinical isolates of Acanthamoeba spp. Although the inhibition effect for all tested concentrations was apparent, and showed 100% eradication of trophozoites of Acanthamoeba castellanii strain at a concentration of 62.5 µM after 24 hr, the strains Acanthamoeba sp. and Acanthamoeba lugdunensis exhibited low sensitivity to hexadecylphosphocholine, even in high concentrations. The determined minimal trophocidal concentrations were 250 µM for Acanthamoeba sp. and 500 µM for A. lugdunensis after 24 hr of exposure. Although hexadecylphosphocholine is a potential agent for treatment of Acanthamoeba keratitis and systemic infections, in clinical practice the possible insusceptibility of the amoebic strain should be considered for optimizing therapy.